Optimization models to support sustainable electricity planning decisions - Pereira, Sérgio (2011)
Over the last decades, models and concepts related to sustainable electricity planning decisions have been changed according to the society, energy policy objectives and concerns. New and clean energy technologies are emerging as major contributors for the achievement of a set of imposed goals, being the energy efficiency combined with renewable energy sources (RES) a key strategy for a sustainable future. Power planning based on optimization models plays an important role for, not only electricity industry decision making process, but also for all processes where complex decision must be made. Following the idea of sustainability combined with the emergence of RES, this study aims to present an on-going research project that involves the development of a set of mathematical models to be used on the electricity planning. Assuming a time period of 10 years and through scenario analysis, the expected impacts in terms of costs and CO2 emissions were evaluated. The behaviour of system when coal and gas fuel price varies is observed. The results put evidence the significant wind power and hydro power impacts on the electricity sector performance and demonstrate importance of these technologies to achieve the European Union goals for the sector.